Artikel - Desak Made Firsia Sastra Putri (JURNAL MEDIKA USADA, 2020)
Background: Hypertension is a disease with the condition of arterial blood pressure increment above normal, the systolic pressure ≥140 mmHg and diastolic ≥85 mmHg. The disease can be prevented and cured with proper hypertension diet and can be done with sufficient knowledge. Purposes: To identifying the sufferers’ knowledge regarding hypertension, hypertension diet obedience, and to analyze the correlation between the knowledge and diet obedience. Methodology: A correlational descriptive research with Cross Sectional approach. Research subjects are the elderly above 60 (sixty) years old. Spearman Rank Correlation Statistic test are applied with 5% degree of error and p value under 0,05. Result: Respondent possess 59,71% of a good knowledge, 30,77% of enough knowledge and 9,62% of less knowledge of hypertension. Obedience level shows that 51,92% respondent are obedient, 34,62% are enough obedient and 13,46% less obedient to hypertension diet. Spearman Rank statistic test shows 0,887 of value and p-value of 0,000 which mean a positive correlation between knowledge and diet obedience of hypertension. Summary: The more educated respondent regarding hypertension are correspond to the obedience to consuming hypertension diet.